2021
DOI: 10.47059/revistageintec.v11i2.1868
|View full text |Cite
|
Sign up to set email alerts
|

Irrational Behaviour and Stock Investment Decision. Does Gender Matter?

Abstract: The research aims to examine the influence of irrational behaviour on stock investment decision, specifically, anchoring, disposition effect, home bias, herding, overconfidence and the risk perception. The research further investigates the moderating role of gender between irrational behaviour and stock investment decision. Finally, it reveals which irrational behaviour is most prevalent. A survey collected the primary data from 425 individual investors. The survey evidence shows that, of six irrational behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…The impact of disposition effect on investment is strong in long position rather than short position (Madaan and Singh 2019). The investors that are following the disposition effect would be likely to make more investment decisions (Siraji et al 2021;Ahmed et al 2022). However, Adil et al (2022) found an insignificant influence of disposition effect on investment choices.…”
Section: Disposition Effect and Investment Decisionsmentioning
confidence: 90%
See 1 more Smart Citation
“…The impact of disposition effect on investment is strong in long position rather than short position (Madaan and Singh 2019). The investors that are following the disposition effect would be likely to make more investment decisions (Siraji et al 2021;Ahmed et al 2022). However, Adil et al (2022) found an insignificant influence of disposition effect on investment choices.…”
Section: Disposition Effect and Investment Decisionsmentioning
confidence: 90%
“…It impairs the quality of investment performance, investment decisions, and risk perception (Ahmad and Shah 2020). Sometimes, the overconfidence bias due to irrationality of investors adversely impacts the investment decisions (Siraji et al 2021). This overconfidence bias distorts investors' rationality in Pakistan and leads them to make more frequent but inefficient investment decisions (Naveed and Taib 2021).…”
Section: Overconfidence Bias and Investment Decisionsmentioning
confidence: 99%
“…Keirasionalan investor yang disebabkan oleh behavioral biases merupakan penyebab umum investor cenderung menjauh dari pengambilan keputusan investasi yang optimal dan sistematis (Siraji et al, 2021). Selain itu, kemudahan dalam melakukan investasi pada jaman saat ini menjadi salah satu dampak bagi beberapa individu yang mengsalahartikan bahwa investasi merupakan suatu bentuk yang dapat memperoleh keuntungan dalam waktu yang singkat dengan jumlah yang banyak.…”
Section: Pendahuluanunclassified
“…According to Siraji, Nazar and Ali (2021), an investor's gender influences their behavioral biases. Additionally, Grable and Lytton (1999) state that the primary issue behind many financial decisions is thought to be a lack of financial risk tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of professionals with high levels of financial knowledge will be a focal issue. So, this review is important as there were only a few attempts that have been made to address topics relevant to the current study within Sri Lanka considering different respondent samples (Amarasinghe, 2019;Kumari, 2020;Siraji, Nazar & Ali 2021). However, there were no research studies found out analysing on investment behavior of finance/accounting professionals who can be more rational when taking their investment decisions than normal household individuals.…”
Section: Introductionmentioning
confidence: 99%